Analisis Budaya Organisasi: Solusi Memperbaiki Produktivitas Tim Di PT Garuda Airline - Harmen, Hilma; Samosir, Julianty; Sianturi, Gracia Inri; Tanjung, Pitri Damayanti; Tarigan, Dea Divella Br; Ramadhani, Suci; Satria, Khosyi Juan (CV. ITTC INDONESIA, 2025)
PT Garuda Indonesia, as one of the national airlines, faces significant challenges in maintaining team performance and productivity. The main problem lies in the weak and inconsistent implementation of organizational culture aligned with corporate governance principles. This issue leads to decreased work motivation, reduced communication effectiveness, and misalignment between company values and employee behavior, resulting in suboptimal team productivity and overall operational performance.This study aims to analyze the influence of organizational culture on team productivity and provide strategic solutions for PT Garuda Indonesia to improve performance effectiveness through the implementation of a corporate governance-based organizational culture.This research employs a qualitative approach using a literature review method. Data were collected through a comprehensive analysis of various secondary sources, including scientific articles, books, company reports, policy documents, and media publications relevant to organizational culture and productivity in the aviation sector. The analysis technique involved comparing empirical findings and theoretical perspectives to identify the relationship between organizational culture implementation, corporate governance, and team productivity.The findings indicate that a weak organizational culture can hinder teamwork and productivity. Conversely, a strong, disciplined organizational culture based on Good Corporate Governance values can enhance effectiveness, efficiency, and individual accountability within teams. Corporate transparency and strict enforcement of ethical standards also play an essential role in strengthening a sustainable organizational culture at PT Garuda Indonesia.